FINANCIAL SUPPORT AND ETHICS IN SCIENTIFIC PUBLICATIONS - Shirley Donizete Prado (Universidade do Estado do Rio de Janeiro, 2014)
A considerable number of recent publications have put focus on topics related to science in Brazil. Graduate programs, researchers and scientific journals have been the object of numerous comprehensive reviews because of the necessary assessment of the activities, agents and rules of the games under which this field of life acts. Different types of interests cross the scientific field, especially those relating to the financing agents of activities that aim at disseminating and sharing the results of scientific researches. DOI 10.12957/demetra.2014.10827